An improved DRBL AlGaN/GaN HEMT with high power added efficiency. (January 2019) - Jia, Hujun; Zhu, Shunwei; Hu, Mei; Tong, Yibo; Li, Tao; Yang, Yintang
Abstract: An improved DRBL AlGaN/GaN HEMT (IDRBL HEMT) with high power added efficiency is proposed and its mechanism is studied by co-simulation of ADS and TCAD software. The barrier layer on both sides of the gate of the new structure has a recessed layer. The simulation results show that the optimized IDRBL HEMT has a large breakdown voltage, a small gate-source capacitance and a large power added efficiency. The maximum PAE obtained from IDRBL HEMT was 53.30%, while the PAE of DRBL HEMT was 36.02%. Therefore, the HEMT of the IDRBL structure has great application prospects in the microwave and radio frequency fields.